Закономірності росту деревних ліан родини Vitaceae Juss. в умовах інтродукції в Правобережному Лісостепу України - Makovskyy, V.V.; Vakhnovska, N.H. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to find out the features of the growth and development of vegetative shoots of woody lianas of the Vitaceae Juss. family depending on the specific features and conditions of vegetation during introduction in the Right-Bank of Forest-Steppe of Ukraine. Material and methods. The subject of the study is the woody lianas of the genus Parthenocissus Planch. and Ampelopsis Michx. of the Vitaceae family. The investigations were carried out during the vegetation period of 2014 at the expositioncollection section “Climbing plants” of the collection fund of the M.M. Gryshko National Botanical Garden of the NAS of Ukraine according to generally accepted methods. The processing of the results was carried out by methods of statistical estimation of the average data in the Microsoft Excel (2007), the correlation analysis – on the basis of Internet resources. Results. Correlation dependence of growth rates and development of vegetative shoots on temperature and relative humidity of air is established. The most intensive growth of all representatives falls on periods with high temperatures. It was found that a prolonged absence of precipitation could have a negative effect on the growth of Ampelopsis genus lianas. Growth of vegetative shoots of wood lianas of the genus Ampelopsis is due to intercalary growth, and representatives of the genus Parthenocissus – due to the apical growth of shoots, and this feature is specific within the genus. The highest values of the annual increment of vegetative shoots are reached by woody vines A. brevipedunculata, and the smallest – P. tricuspidata ‘Veitchii’. Conclusions. As a result of the conducted research, it was found that the highest values of annual growth of vegetative shoots reach the woody vines A. brevipedunculata, and the smallest – P. tricuspidata ‘Veitchii’. The most intensive growth and development of shoots of all investigated representatives falls on periods with high mean daily temperature. Prolonged absence of precipitation in late July, early August, contributed to a slowing down of the growth and development of the studied introducers of the genus Ampelopsis. At the same time, this did not significantly affect the overall growth of shoots, because their growth and development is carried out, to a greater extent, due to the extension of interstices. Growth of vegetative shoots in the species and forms of tree lianas of the genus Parthenocissus is achieved, mainly due to the increase in the number of internodes, so they did not suffer from adverse effects under the same conditions.